EAZY PASSPORT SERVICES AND IMMIGRATION POLYTECHNIC SOCIALIZATION AT SAM RATULANGI UNIVERSITY - Habbi Firlana; Pascalis Danny Kristi Wibowo (Polteknik Imigrasi, 2022)
The Eazy Passport service is one of the innovations made by the directorate general of immigration to improve passport services to the public collectively, through representatives of immigration offices spread throughout Indonesia. The Eazy Passport service in the North Sulawesi region is carried out by the Immigration Office class I TPI Manado which has been scheduled at the request of Sam Ratulangi University, during this activity the immigration office class I TPI Manado Together with Lecturers and Cadets of the Immigration Polytechnic who are carrying out the Bumi Phura Job Training as well as introducing The Immigration Polytechnic as one of the official schools under the Ministry of Law and Human Rights which focuses on the field of immigration, this activity was presented by Lecturers and Cadets of the Immigration Polytechnic to the Academic Community of Sam Ratulangi University Faculty of Law which was attended by officials, lecturers, staff and students. In carrying out this activity the enthusiasm of the Sam Ratulangi University academic community in making passports exceeded expectations from the class I immigration office TPI Manado as many as 56 people and the responses of the participants in the immigration polytechnic socialization were quite good with many questions related to the registration process, besides that there were discussions related to cooperation opportunities in the field research and independent learning independent campus..